POTENSI ANTIINFLAMASI JUS BUAH MANGGIS (Garcinia mangostana) TERHADAP DENATURASI PROTEIN IN VITRO - Muhammad Rizky Tri Aditya; Donna Marisa; Eko Suhartono (Berkala Kedokteran, 2015)
Protein denaturation is a cause of inflammation. Autoantigens produced in diseases linked with inflammation are thought to be caused by protein denaturation. Mangosteen fruit (Garcinia mangostana) is used widely in Southeast Asia as an alternativemedicine because of its strong antioxidant property, thus it potentially has an antiinflammatory effect. The aim of this study is to test the anti inflammatory potency of mangosteen juice. This is a quasi experimental study with non randomized posttest-only with control group design method, using reaction model of inflammation consisted of two groups: mangosteen juice as the test group and natrium diclofenac as the standard group, divided into 10%, 20%, and 30% concentration. IC50 value is used to determine the anti-inflammatory potency of mangosteen juice as protein denaturation inhibitor. The result of this study indicate that the mangosteen fruit juice has the IC50 value of 16,91% (r = 0,965), whereas for diclofenac sodium by 11,87% (r = 0,866). A positive value of r indicates a positive relation between concentration and anti inflammatory potency. The result shows that mangosteen juice has a potential as a protein denaturation inhibitor.Keywords: protein denaturation, antiinflammation, mangosteen.